Chrysotoxum vernale LOEW 1841 - Samin, Najmeh; Sakenin, Hamid (Zenodo, 2015)
Chrysotoxum vernale LOEW, 1841 Material examined : West Azarbaijan province, Khoy, 38°33'N 44°57'E, 1 ♂, 15-17 May 2012. Distribution outside Iran : Fennoscandia south to the Pyrenees; from Britain (southern England) eastwards through most of Europe into Asia almost to the Pacific. : Published as part of Samin, Najmeh & Sakenin, Hamid, 2015, A faunistic study on the hoverflies (Diptera: Syrphidae) from West Azarbaijan province, Iran, pp. 393-401 in Beiträge Zur Entomologie = Contributions to Entomology 65 (2) on page 396, DOI: 10.21248/contrib.entomol.65.2.393-401, http://zenodo.org/record/5371302